The use of Hermetia illucens and Chrysomya chloropyga larvae and pre-pupae meal in ruminant nutrition - Haasbroek, Pierre (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.